Pengaruh Topografi dan Kesarangan Batuan Karbonat terhadap Warna Tanah pada Jalur Baron-Wonosari Kabupaten Gunungkidul, DIY - Mulyanto, Djoko; Surono, S (Forum Geografi, 2009)
Western part of the East Jawa Southern Mountains, which is distributed from Parangtritis, Yogyakarta to Pacitan Bay is the Gunung-Sewu Hills. The carbonate rocks on the Baron-Wonosari transect has some litofacies, and the soils overlying the rocks show some color varieties. Topography of Baron-Wonosari transect can be divided into two areas: southern part (Baron-Mulo) and northern part (Mulo-Wonosari). The southern part is a hilly land, whereas the northern part is a lowland plain. Soils on the southern part are dominated by red soils group, whereas on the northern part dominated by black soils group. The phenomenon is very interesting to be studied. The aim of research was to study relationship of soil colour with topography and pores of underlying carbonate rocks. Methods consist of landform especially topography observation, and soil colour by Munsell Soil Colour Chart, whereas laboratory analysis namely micro porosity and geochemical of carbonate rock. The results showed that micro pores of rocks have no effect to the soil colour formation. However, secondary pores (macro and mega) be suggested influent on red soil formation. Concentration of iron (Fe) and mangan (Mn) elements of carbonate rock have no effect on the formation of soil colour. Topography and rock secondary porosity be estimated have a role as controlling factors on the formation of soil colour by leaching process mechanism. An area, which has a high leaching capacity tend to be found much of red soils, whereas an area which has a low leaching capacity will be formed black soils.